The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4103/0019-5413.61768
|View full text |Cite
|
Sign up to set email alerts
|

Hook plate for medial clavicle fracture

Abstract: Medial clavicle fractures are the least common type of clavicular fractures. Although rare, such injuries deserve rapid diagnosis and effective treatment to avoid future complications. An optimal, standardized operative treatment has not been yet established. We report a case of medial clavicle fracture, where primary operative treatment was indicated due to gross dislocation. An open reduction and osteosynthesis with a modified hook plate was performed, leading to an excellent postoperative outcome after a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
0
27
0
3
Order By: Relevance
“…This plate complementary maintains reduction of anterior-posterior dislocation and acromioclavicular joint width and can be used for the treatment of acromioclavicular luxation and fractures of the lateral clavicle [15]. In some cases this device also has been used for sternoclavicular joint dislocations [16]. After modification of the plate in 2005 it is also available with locked screws, which gives extra stability for the treatment of fractures of the lateral clavicle and makes minimal invasive application of the plate with the use of only two screws possible.…”
Section: Introductionmentioning
confidence: 99%
“…This plate complementary maintains reduction of anterior-posterior dislocation and acromioclavicular joint width and can be used for the treatment of acromioclavicular luxation and fractures of the lateral clavicle [15]. In some cases this device also has been used for sternoclavicular joint dislocations [16]. After modification of the plate in 2005 it is also available with locked screws, which gives extra stability for the treatment of fractures of the lateral clavicle and makes minimal invasive application of the plate with the use of only two screws possible.…”
Section: Introductionmentioning
confidence: 99%
“…Gill et al [6] reported using a modified hook plate for a medial clavicle fracture in a 21-year-old female. Although clinical results were satisfactory, the plate crossed the SC joint, where high bending forces occur during shoulder motion.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is not a commonly accepted surgical fixation method. Pins, wires, small fragment reconstruction plates, dynamic compression and hook plates and plates manufactured specially for this anatomical site are all used [10,[20][21]. Plate screw fixation seems to be safer than pin or wire fixation [22].…”
Section: Discussionmentioning
confidence: 99%